What is the question? Do you want the distance between the hyperbola and the point? Or did you mean the line y=(1/4)x-2? Do you want the equation of the perpendicular? We can't give you an answer if you don't state a question.

Posted on Nov 22, 2013

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

f(x) + g(x) would just be the two functions added together.

f(x) + g(x) = 7x 2?4x+8 + (?6+4x?7x 2)

Sorry, I don't understand your initial functions.

Good luck.

Paul

f(x) + g(x) = 7x 2?4x+8 + (?6+4x?7x 2)

Sorry, I don't understand your initial functions.

Good luck.

Paul

Feb 07, 2017 | Homework

Do yourself a favor and get rid of the negative signs: Multiply the inequality by (-1) and change its direction. It will look like

**x^2+4x+12<0**

Complete the square x^2+4x +4 +8 = (x^2+4x+4) +8=(x+2)^2+8 as you can see, the first term (x+2)^2 is always positive, and +8 is also positive. So their sum is positive and never be less than 0.

**x^2+4x+12 is ALWAYS positive.**

Your inequality has no solutions.

Complete the square x^2+4x +4 +8 = (x^2+4x+4) +8=(x+2)^2+8 as you can see, the first term (x+2)^2 is always positive, and +8 is also positive. So their sum is positive and never be less than 0.

Your inequality has no solutions.

Jul 15, 2014 | Office Equipment & Supplies

if you mean {7(2)2+[(3-2)-4x(3)]2} or 7(2)2+[(3-2)-4x(3)]2

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

Jun 12, 2013 | Office Equipment & Supplies

See captured image below

Mar 01, 2011 | Office Equipment & Supplies

=>2x+3=0 ; taken x as common and 4-2=2 i.e. x(4-2) = 2x

=>2x=-3 ; +3's moved on the right-hand side, so it becomes -3

=>x=-3/2 ; 2 has been moved to the right-hand side and divided with -3 i.e 1/2 multiplied by -3 = -3/2

Good luck.

Thanks for using

Aug 13, 2010 | SoftMath Algebrator - Algebra Homework...

Hii,you can use the following solution
x^3 - 4x^2-12x=0
x(x^2-4x-12)=0
replacing -4x from -6x+2x
x(x^2-6x+2x-12)=0

Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

May 05, 2010 | Vivendi Excel@ Mathematics Study Skills...

Hello,

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is** added **to 4x. If I want the term in y alone on one side I perform the** inverse operation of addition**, a **substraction**. I subtract 4x from both sides.

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

**3y= - 4x+6**

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is**multiplied** by the number 3. To isolate y I have to perform the **inverse operation** of the multiplication, namely the division by 3

3y/3 =(-4x+6)/3. The left hand side is just y

**y= (-4x+6)/3.**

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

**y= -(4/3)*x +2.**

Hope it helps.

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is

3y/3 =(-4x+6)/3. The left hand side is just y

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

Hope it helps.

Oct 22, 2009 | Texas Instruments TI-89 Calculator

Hello,

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

Oct 01, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

Aug 19, 2017 | Computers & Internet

57 people viewed this question

Usually answered in minutes!

×